Hypocomplementemia is associated with worse renal survival in ANCA-positive granulomatosis with polyangiitis and microscopic polyangiitis - Deshayes, Samuel (PLoS One, 2018)
Recent data suggest the existence of a complement alternative pathway activation in the pathogenesis of antineutrophilic cytoplasmic antibody (ANCA)-associated vasculitis (AAV), a condition that remains poorly understood. This study aims to assess the clinical characteristics and outcomes of granulomatosis with polyangiitis (GPA) and microscopic polyangiitis (MPA) patients with regard to their plasma complement levels at diagnosis. A retrospective monocentric study carried out at Caen University Hospital led to the identification of proteinase-3- or myeloperoxidase-ANCA-positive GPA and MPA patients from January 2000 to June 2016 and from September 2011 to June 2016, respectively. All patients with available C3 and C4 levels at diagnosis were included. Patients were categorized in the hypocomplementemia group if their C3 and/or C4 levels at diagnosis were below the lower limit of the normal range. Among the 76 AAV patients (43 GPA, 33 MPA), 4 (5%) had hypocomplementemia, and the 72 remaining patients exhibited normal plasma complement levels. All 4 hypocomplementemia patients had renal involvement. Hypocomplementemia was followed in 1 patient whose post-treatment complement level normalized within 1 month. Among all clinical and ANCA specificity, including relapse-free survival (p = 0.093), only overall and renal survival rates were significantly lower in the hypocomplementemia group (p = 0.0011 and p<0.001, respectively). Hypocomplementemia with low C3 and/or C4 levels at GPA or MPA diagnosis may be responsible for worse survival and renal prognosis. These results argue for larger and prospective studies to better determine the epidemiology of the disease and to assess complement-targeting therapy in these patients.